Impact of E-Leadership on Service Delivery in Kenya: A Case of Public Universities - Wanjara, Amos Otieno; Ogembo, Paul Okeyo (ETDC: Indonesian Journal of Research and Educational Review, 2024)
Electronic leadership is basically becoming a norm in contemporary organizations. Despite the effectiveness and efficiency attached to e-leadership, its extent of adoption seems to be at the infancy stage in most of Kenyan Organizations. The purpose of this paper was to assess the impact of e-leadership on Service delivery in Kenya’s Public Universities. The objectives of the study were: to establish the level of adoption of e-leadership in Kenya’s Public Universities, to establish the impact of e-leadership on communication in the public universities and to establish effects of e-leadership on service delivery in Kenya’s Public Universities. The study adopted a Meta-analysis of empirical literature on the topic. The study was underpinned by Technology Acceptance Model by Davis (1989). The study established variability in the level of embracement of e-leadership amongst the universities, that there was a strong positive relationship between e-leadership and service delivery, that e-leadership enhances faster and effective communication. The study findings have implications on the corporations’ need to embrace e-leadership for their effectiveness.